Engaged Fatherhood for Men, Families and Gender Equality Healthcare, Social Policy, and Work Perspectives - Grau Grau, Marc; las Heras Maestro, Mireia; Riley Bowles, Hannah (Contributions to Management Science, 2022)
This aim of this open access book is to launch an international, cross-disciplinary conversation on fatherhood engagement. By integrating perspective from three sectors-Health, Social Policy, and Work in Organizations-the book offers a novel perspective on the benefits of engaged fatherhood for men, for families, and for gender equality. The chapters are crafted to engaged broad audiences, including policy makers and organizational leaders, healthcare practitioners and fellow scholars, as well as families and their loved ones.